Estrategias lúdicas y su influencia en el proceso de enseñanza aprendizaje online de los niños de 4to grado educación general básica de la Escuela de Educación Básica "Ciudad de Babahoyo" del cantón Babahoyo provincia Los Ríos, período lectivo 2020 – 2021 - Cando Otacoma, Elvia Vanessa (2021)
This work carried out in the School of Basic Education "Ciudad De Babahoyo" and considering the way that playful strategies and their use can contribute in the teaching-learning process in online classes, as the level of attention of students in the online classes is affected. hours of classes, the observation technique was used, filling out a file of the same for the collection of information from the teacher and the students, diagnosing the use of playful strategies and the way to distribute their online teaching to the students. Given the scant application of playful strategies in the virtual classroom and the demands of today's society, which is asking us for an essential transformation in the educational process that allows students to develop and improve their capacities, assuming responsibility in their participation in the activities at hand. perform both inside and outside of online classes. The development and application strategies carried out in the project focus on children who feel free to express their ideas and are not governed by a type of rule or norm where the student can grow individually and socially. since the playful strategies are designed to create an environment of harmony between the teacher and the students, putting into practice fun and enjoyable activities in which they can include content, themes or messages, becoming a means for the student to relate to their environment, their personality, thus allowing them to get to know the world and develop their creativity and increase their knowledge. An investigation was carried out where a teacher survey was applied whose results were expressed in graphs with their corresponding observation, in the proposal some playful strategies are developed that can be applied in virtual classes, improving the level of attention between the student and the teacher.